Dual Tumor-Targeting Nanocarrier System for siRNA Delivery Based on pRNA and Modified Chitosan - Lin Li; Xiaoqin Hu; Min Zhang; Siyu Ma; Fanglin Yu; Shiqing Zhao; Nan Liu; Zhiyuan Wang; Yu Wang; Hua Guan; Xiujie Pan; Yue Gao; et al. (Elsevier, 2017)
Highly specific and efficient delivery of siRNA is still unsatisfactory. Herein, a dual tumor-targeting siRNA delivery system combining pRNA dimers with chitosan nanoparticles (CNPPs) was designed to improve the specificity and efficiency of siRNA delivery. In this dual delivery system, folate-conjugated and PEGylated chitosan nanoparticles encapsulating pRNA dimers were used as the first class of delivery system and would selectively deliver intact pRNA dimers near or into target cells. pRNA dimers simultaneously carrying siRNA and targeting aptamer, the second class of delivery system, would specifically deliver siRNA into the target cells via aptamer-mediated endocytosis or proper particle size. To certify the delivering efficiency of this dual system, CNPPs, pRNA dimers alone, chitosan nanoparticles containing siRNA with folate conjugation and PEGylation (CNPS), and chitosan nanoparticles containing pRNA dimers alone (CN) were first prepared. Then, we observed that treatment with CNPPs resulted in increased cellular uptake, higher cell apoptosis, stronger cell cytotoxicity, and more efficacious gene silencing compared to the other three formulations. Higher accumulation of siRNA in the tumor site, stronger tumor inhibition, and longer circulating time were also observed with CNPPs compared to other formulations. In conclusion, this dual nanocarrier system showed high targeting and favorable therapeutic efficacy both in vitro and in vivo. Thereby, a new approach is provided in this study for specific and efficient delivery of siRNA, which lays a foundation for the development of pRNA hexamers, which can simultaneously carry six different substances. Keywords: dual tumor-targeting nanocarrier system, siRNA, chitosan, pRNA, folate, aptamer